PENGGUNAAN MEDIA KANTONG BILANGAN UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MATERI PENGURANGAN PADA SISWA KELAS 1-A SDN TLOGOMAS 2 KOTA MALANG - Endah Dewi Lestari; Trisakti Handayani; Sulistiani Sulistiani (Universitas Sarjanawiyata Tamansiswa, 2019)
This study had an objective to determine the application and improvement of students' abilities in mathematics learning of subtraction material of two integers in class 1-A of Tlogomas 2 Elementary School in Malang City. The approach used in this study was a qualitative approach, in which the data obtained was objective data (by the reality in the field). The data collected in this study were taken during the learning process in class discussing subtraction material, both pre and post action given by using the number bag media. This type of research was classroom action research (classroom action research) designed for researchers and teachers, to solve problems that occurred in the classroom relating to the process and results of learning. The subject of this study were grade 1-A students at Tlogomas 2 Elementary School, Malang City, which consists of 28 students, 16 male students, and 12 female students. The results of students' abilities in a material reduction in pre-action are 25%. While the results of students' abilities after the post-action with number bag media, in the first cycle reached 67.9% and in the second cycle of 85.7%. Based on the research that had been done, it showed that the use of number bag media could improve students' abilities in the reduction material.